P225 David against Goliath: direct comparison of hand-held bowel sonography and magnetic resonance enterography for diagnosis of Crohn's disease. (21st January 2022) - Rispo, A; Mainenti, P P; Testa, A; de Sire, R; Imperatore, N; Nardone, O M; Ricciolino, S; Patturelli, M; Olmo, O; Calabrese, G; Castiglione, F
Abstract: Background: The diagnosis of small bowel Crohn's disease (CD) is mainly performed by ileo-colonoscopy (IC), while the assessment of its extension can be achieved non-invasively by using magnetic resonance enterography (MRE) and bowel sonography (BS) in view of a very concordant agreement about diagnostic accuracy. More recently, hand-held sonography has been used effectively in cardiological and orthopaedical diagnostic settings, while data about its use for CD diagnosis are still scarce. The aim of this pilot study was to evaluate the diagnostic accuracy of hand-held BS (HHBS) in comparison with MRE for the diagnosis of CD. Methods: From September 2019 to June 2021, we prospectively studied 85 consecutive subjects who attended our third level IBD Unit for suspected CD. All patients underwent IC (as gold standard for CD diagnosis), HHBS (VScan, dual probe, 5–7.5 MHz; General Elelectric®) and MRE in a random order and blind way. MRE was assumed as reference standard for defining the extension of small bowel CD. Bivariate correlation about CD extension between MRE and HHBS was calculated by Spearman's coefficient (r). To test the consistency between MRE and HHBS for CD location and complications (strictures, abscesses, fistulas) the Cohen's k measure was applied. A p value of 0.05 was considered significant. Results: The diagnosis of small bowel CD was made in 48 out of 85 subjects (56%), whereas the remaining 37 subjects received a different diagnosis. Sensitivity, specificity, positive and negative predictive values for CD diagnosis were 87% (95%CI 74–95%), 91% (95%CI 78–98%), 91% (95%CI 78–96%), 88% (95%CI 77–93%) for HHBS (TP 42, TN 34, FP 3, FN 6) and 92% (95%CI 80–97%), 95% (95%CI 81–99%), 94% (95%CI 81–98%), 91% (95%CI 85–97%) for MRE (TP 44, TN 35, FP 2, FN 4), without significant differences (p=N.S.). On the other hand, MRE was superior to HHBS in defining CD extension (r=0.67; p<0.01) and location (k = 0.81; p<0.01). Also, MRE showed a better diagnostic performance than HHBS for detecting strictures (k=0.75; p<0.01), abscesses (k=0.68; p<0.01) and fistulas (k=0.65; p<0.01). Conclusion: HHBS and MRE are two accurate and non-invasive procedures for the diagnosis of CD, even if MRE appears to be more sensitive in defining the extension, location and intestinal complications. HHBS could be used as effective ambulatory (or out-of-office) screening tool for selecting the patients to submit to MRE examination because of high probability of CD diagnosis.